Using RNA Sequencing Data to Analyze the \(tRNA^{Cys}\) Processing under Salt Stress in Bacillus subtilis Spore Outgrowth - Hernández , Iván Arvizu; Flores , José Luis Hernández; Pérez , Juan Caballero; Sánchez , Héctor Gutiérrez; López , Miguel Ángel Ramos; Gómez , Sergio Romero; Hernández , Andrés Cruz; Gutierrez , Carlos Saldaña; Hidalgo , Erika Álvarez; Jones , George H.; Guillén , Juan Campos (Research Advances in Microbiology and Biotechnology Vol. 5, 2023)
The present study identify several categories of tRNACys species in dormant spores and during the first minutes of their conversion into growing cells. This study provides valuable insights into tRNACys processing during this state of transition. The molecular mechanisms of transfer RNA (tRNA) accumulation during sporulation in spore-forming bacteria must be studied as a top priority because tRNAs are crucial for protein synthesis during spore germination and outgrowth. To comprehend long-term stress survival, it is crucial to understand tRNA processing in these circumstances, which has not been thoroughly studied. To gain further insight into tRNA processing during spore germination and outgrowth, the expression of the single copy tRNACys gene was analyzed in the presence and absence of 1.2 M NaCl in Bacillus subtilis using RNA-Seq data obtained from the Gene Expression Omnibus (GEO) database. The CLC Genomics work bench 12.0.2 (CLC Bio, Aarhus, Denmark, https://www.qiagenbioinformatics.com/) was used to analyze reads from the tRNACys gene. The results show that spores store different populations of tRNACys-related molecules. One such population, representing 60% of total tRNACys, was composed of tRNACys fragments. Half of these fragments (3´-tRF) possessed CC, CCA or incorrect additions at the 3´end. tRNACys with correct CCA addition at the 3´end represented 23% of total tRNACys, while with CC addition represented 9% of the total and with incorrect addition represented 7%. While an accumulation of tRNACys precursors was induced by upregulation of the rrnD operon under the control of \(σ\)A -dependent promoters under both conditions investigated, salt stress produced only a modest effect on tRNACys expression and the accumulation of tRNACys related species. The results reported here using RNA-Seq and data analysis provide new insights into the dynamic changes in the sub-populations of RNA species related to tRNACys molecules in dormant spores and during spore germination and outgrowth in the presence and absence of 1.2 M NaCl.